2010
DOI: 10.1021/op100103v
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Large-Scale Synthesis for a 4H-imidazo[5,1-c][1,4]benzoxazine-3-carboxamide Derivative for Depression and Anxiety

Abstract: The development and scale-up of an optimized synthesis for a novel drug candidate for depression and anxiety is presented. The updated synthesis represents a convergent and efficient four-stage approach to the API, overcoming high cost of goods (COG), general lack of convergence, and low yield of previous routes. A lower cost of goods resulted from using 3-nitrosalicylaldehyde as a starting material and introducing the expensive side chain (2-methyl-5-(piperazin-1-yl)quinoline) at a later stage. Green chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…According to a recent ICH guidance Q3C (R8) [ 27 ], 2-MeTHF and CPME belong to solvent classes 3 and 2, respectively. Thus, they are recognized as “greener alternatives” to VOCs [ 28 , 29 ], and their use has been strongly advocated in the synthesis of drugs and drug intermediates by the ACS Green Chemistry Pharmaceutical Roundtable [ 30 , 31 , 32 ]. On this basis, we focused on the use of these solvents for the total synthesis of dimethindene ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent ICH guidance Q3C (R8) [ 27 ], 2-MeTHF and CPME belong to solvent classes 3 and 2, respectively. Thus, they are recognized as “greener alternatives” to VOCs [ 28 , 29 ], and their use has been strongly advocated in the synthesis of drugs and drug intermediates by the ACS Green Chemistry Pharmaceutical Roundtable [ 30 , 31 , 32 ]. On this basis, we focused on the use of these solvents for the total synthesis of dimethindene ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…That washing with aqueous Rochelle salt after hydrolysis resulted in poor separation of layers suggested that the order in which these processes were performed was very important for ease of operation and reducing the reaction time (Table , entry 3). In the Wittig reaction ( 6 → 7 ), removal of the byproduct triphenylphosphine oxide is typically a serious problem . We developed an efficient purification method that employed crystallization with n -heptane.…”
Section: Resultsmentioning
confidence: 99%
“…The second order perturbation energy (E 2 ) is the quantitative measure of interactions between donor and acceptors in NBO and is also known as stabilization energy. The higher value of E (2) is reflecting stronger interactions of donor and acceptor and the higher extend of conjugation [25]. The value of E (2) depends on occupancy of donor (i) and acceptor (j), the diagonal elements (orbital energies) and and the off-diagonal Fork matix element, ( , ) [54].…”
Section: Natural Bond Orbital (Nbo) Analysismentioning
confidence: 99%
“…The E (2) analysis of selected donor and acceptor orbitals of S11 in gas phase are given in the Table 4. It shows the pi conjugation resonance in the first benzene ring (arising from pi electrons delocalization) and the primary as well as secondary hyper-conjugation.…”
Section: Natural Bond Orbital (Nbo) Analysismentioning
confidence: 99%
See 1 more Smart Citation